Facebook Usage and Its Impact on Academic Performance of Sri Lankan University Students - De Silva, K.B.N; Dharmasiri, K.S; Budhdadasa, M.P.A.A; Ranaweera, K.G.N.U (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Like many other countries, Sri Lanka has been impacted by the Facebook phenomenon. At the beginning of January 2021, Sri Lanka had 7 646 000 Facebook users or about 35.8 percent of the country’s total population. Facebook usage among university students continues to grow daily, as evidenced by the amount of time spent on social networking sites. Male and female university undergraduates are equally fond of Facebook. The prime intention of the study is to determine the relationship between Facebook usage and the academic performance of Sri Lankan university students. A convenient random sampling technique, the non-probability sampling approach, has been utilised to represent the sample. Moreover, the sample includes 45 (N=45) graduated students of the University of Sri Jayewardenepura. A convenient random sampling technique, the non-probability sampling approach, has been utilised to represent the sample. Due to the covid-19 pandemic situation, data gathering has been done byconducting an online survey; the sample consists of forty-five graduated students from the University of Sri Jayewardenepura. Data analysed using SPSS software (V26); the Pearson Correlation method has been utilised to test the reliability of the question items. In line with the study, it is revealed that university students use Facebook for various reasons, and their intentions also vary. Hence, the academic preferences and motivation for academic works also follow undergraduate students’ dilemmas. In accordance with the hypothesis testing, it is revealed that there is a negative or positive correlation between Facebook usage and the academic performance of university students.